Bibliometric Analysis of Research Trends in Agricultural Soil Organic Carbon Mineralization from 2000 to 2022 - Futao Zhang; Yuedong Liu; Yueling Zhang (Agriculture, 2023)
The change in agricultural soil organic carbon (SOC) at a global scale has a great impact on the soil quality, crop yields, and greenhouse gas concentration in the atmosphere. Plant-derived C input into soil is an effective strategy to increase the SOC; meanwhile, it promotes SOC mineralization. The SOC dynamics after plant-derived C input have received widespread attention in the past 20 years. This bibliometric study was performed to identify the basic characteristics, research output, and knowledge base as well as to understand the research trends and key topics of agricultural SOC mineralization. We collected data from the Web of Science Core Collection databases, with dates ranging from 2000 to 2022. The parameter calculated from the default indicators of bibliometric software tools was used to indicate the contribution of the journal/author/institution/countries. The activity and attractive index were calculated separately to evaluate the relative effort and impact made by a country. The results showed that: (1) the number of articles increased gradually during 2000–2010 and thereafter sharply increased; (2) Soil Biology & Biochemistry was the most representative journal, and agriculture was the most popular subject category; (3) the most productive institution was the Chinese Academy of Sciences, which is based China and cooperates closely with other institutions; (4) although the number of articles from China was the largest, both the cited frequency and activity index were much lower for China than for the USA, which had the highest citation and centrality among countries; and (5) the studies involving agricultural SOC mineralization have primarily investigated the effect of exogenous C and nutrient addition, as well as biotic processes, especially the microbial process. We concluded that there was an increasing trend in research on agricultural SOC mineralization, with a focus on the interaction between SOC and nutrient/microbial communities. The physical processes, such as the association of minerals and occlusion of aggregate and pores, were paid less attention relative to biotic processes despite their importance in SOC mineralization. Through an in-depth analysis of agricultural SOC mineralization research, this study provides a better understanding of development trends that have emerged in this field over the past 22 years. In future studies, more attention should be paid to the physical processes to understand the physical protection mechanism of agricultural SOC mineralization.